Metode AHP Sebagai Pengukur Kinerja Rantai Pasok Beras di Kabupaten Serang - Syaina Ulfah Azhara; Heru Winarno; Muhamad Bob Anthony; Al Fiillian Sah Putra (LPPM Universitas Sangga Buana, 2025)
This study will discuss the application of the SCOR model as a supply chain performance measurement model and the AHP method used for decision making and priority placement in a structured process. In 2023, DISKOUMPRINDAG and DKPP experienced problems due to the increase in the price of basic necessities, especially rice in Serang Regency, based on the recap of the development of the price of basic necessities in Serang Regency in 2023, there was an increase in the price of Kw 1 rice by 22% and Kw 2 by 19%. This situation requires both agencies to play an active role and collaborate in dealing with the price increase. If not handled properly, this condition has the potential to trigger an economic crisis at the regional level. The research method uses the SCOR model and the Analytical Hierarchy Process method. Based on the results of the study, it is known that the performance of the rice supply chain in Serang Regency is in an Average condition with a performance value of 52.23. The source criteria have the most weight of 30% followed by make and plan which are both at 20% after which is deliver with a weight of 13% and return occupies the last place with a weight of 12%. It is hoped that research suggestions can continue to the development stage so that they can ensure increased performance in the supply chain and no decline in performance.